Development of Local Instruction Theory Topics Lowest Common Multiple and Greatest Common Factor Based on Realistic Mathematics Education in Primary Schools - Ditria Yulianti; Ahmad Fauzan (International Journal of Educational Dynamics, 2019)
This study discusses developing a mathematical education (RME) based local theory (LIT) that is valid, practical, and effective on the topic of the lowest common multiple and greatest common factor in grade V of elementary school. The research method used is the type of research design Gravemeijer & Cobb (2013). This research was conducted in three phases, namely conducting experiments, experimenting in class, and conducting a retrospective analysis. Data was collected using document analysis, observation, interviews, field notes, tests, and questionnaires. The collected data was analyzed qualitatively and quantitatively. Based on the research that has been done, LIT has been approved which is valid, practical, and effective for students' mathematical literacy abilities. Students can solve the problems of LCM and GCF with various activities, namely finding multiples and multiples of fellowship, finding factors and factors of fellowship then resolving problems related to daily life. Keywords: LIT, RME, LCM, CGF.